Evaluation of ocular diameter parameters using swept-source optical coherence tomography - Dong, Jing; Yao, Jinhan; Chang, Shuimiao; Kanclerz, Piotr; Khoramnia, Ramin; Wang, Xiaogang (Medicina)
Purpose: To investigate the iridocorneal angle-to-angle (ATA), sclera spur-to-sclera spur (STS), and white-to-white (WTW) ocular diameters and their potential influence on anterior chamber intraocular lens (ACIOL) and implantable collamer lens (ICL) sizing in Chinese subjects by using a swept-source optical coherence tomography system (SS-OCT). Design: A retrospective, observational, cross-sectional study. Methods: In 60 right eyes (60 subjects), the ATA, STS, and WTW were measured in six axes (0°-180°, 30°-210°, 60°-240°, 90°-270°, 120°-300°, and 150°-330°) using SS-OCT. The ACIOL and ICL sizes were calculated based on horizontal and vertical axes anterior segment data. A paired sample t-test was used to test the differences in each parameter across the six axes, the potential difference between each pair of parameters in a given axis, and the artificial lens size difference between the horizontal and vertical directions. Pearson’s correlation analysis was used to determine the potential correlation between age and AL, WTW, STS, and ATA distances. Results: ATA and STS were the longest on the vertical and shortest on the horizontal axis, while WTW was similar on both axes. These three parameters differed only in the vertical axis (F = 4.910, p = 0.008). ATA and STS were by 0.23 ± 0.08 mm (p = 0.005) and 0.21 ± 0.08 mm wider (p = 0.010) than WTW, respectively. ICL size was 0.27 ± 0.23 mm smaller when based on the horizontal than on the vertical axis parameters (p < 0.001), while ACIOL remained similar (p = 0.709). Age correlated negatively and axial length positively with all measured values. ATA, STS, and WTW correlated positively in the same axis (all p < 0.001). Conclusions: ATA and STS were longer in the vertical than in the horizontal direction, while WTW measurements remained similar. ATA and STS diameters more accurately depicted anatomic relationships for phakic IOL sizing than WTW.